Chapter The Promise of Laboratories An Introduction to Digital Humanities Laboratories in the 21st Century - Pawlicka-Deger, Urszula (Taylor & Francis, 2024)
This book is about digital humanities laboratories, places where the humanities take up new digital and computational technologies for teaching and research, which often grow out of-or turn into-other contemporary labs configurations: research software engineering labs, digital heritage labs, feminist labs, and social labs. In this introduction, the editors present the goal of the volume, which is to discuss the concept of a laboratory in digital humanities from a broad range of perspectives: epistemological, infrastructural, technological, and socio-cultural. This book offers a reflection on how to interrogate the organisational structures of digital humanities, how to reimagine a "critical laboratory" with great sensitivity towards racial, gender, and indigenous issues, and what can be offered to other humanities fields interested in laboratories (e.g., science and technology studies, media studies, and cultural heritage studies). Laboratories have become an important lens for investigating the development of the field of digital humanities and its connections with science, technology, industry, and society, drawing on interdisciplinary approaches from science and technology studies, infrastructure studies, philosophy of technology, feminism, postcolonial studies, and critical digital pedagogy. This collection aims to pave the way toward "laboratory studies" as a new research direction in digital humanities.